A Comparative Study of Role Efficacy among Employees in Selected Manufacturing and IT Firms - Kaur , Rupinder Bir (Gyan Management Journal, 2018)
As defined by Pareek, role efficacy is the potential effectiveness of the role of an individual in an organization. It involves role making, role centering and role linking. Studies have shown the significance of role efficacy and its understanding in an organization. Role efficacy has proved to be a factor for organizational citizenship, psychological involvement of the employees etc. The resulting performance of employees signifies the need of the present study. The study focuses on comparison between role efficacy between manufacturing and IT firms. It further attempts to study the relationship between demographic variables and Role efficacy in two types of firms.
Keywords: Role Efficacy; Manufacturing firms; IT firms